THE INFLUENCE OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP, GROWTH OPPORTUNITIES AND PROFITABILITY ON ACCOUNTING CONSERVATISM WITH LEVERAGE AS A MODERATING VARIABLE - Dawsaryan A.S, Muhammad Rifkan; Abdani, Fadlil (Jurnal Riset Akuntansi Politala, 2025)
This study aims to analyze the effect of managerial ownership, institutional ownership, growth opportunities, and profitability on accounting conservatism with leverage as a moderating variable in technology companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative descriptive method using secondary data obtained through the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id. The sample of this study included a total of 46 technology companies and those that met the criteria were 12 companies for the period 2021-2023. The analysis method used is panel data regression with a moderation model. The results of hypothesis testing from this study prove that growth opportunities and profitability have a significant effect on accounting conservatism. Institutional ownership affects accounting conservatism but is not significant. While managerial ownership shows an influence even though it is not significant. Leverage can significantly influence management and institutional ownership on accounting conservatism, but cannot moderate the effect of growth opportunities and profitability on accounting conservatism.